A história da Educação de Jovens e Adultos (EJA): uma proposta para o ensino de condição de existência de triângulos utilizando material manipulável - Vaz, Pedro Itallo (2024)
In this dissertation, a brief account of the history of Adult and Youth Education (EJA), the EJA curriculum, and a proposal for teaching the conditions for the existence of triangles to this audience will be presented. The aim of this teaching proposal is to encourage student integration, create meaning for what the students are studying, and, consequently, promote actions that provide motivation opportunities so that students feel more enthusiastic about studying mathematics using playful activities. Moreover, with this teaching method, we can achieve the four strands of meaningful mathematical learning: experimenting, conjecturing, formalizing, and generalizing.